Inter-Laboratory Comparison of Accredited Laboratories in Terms of Benchmarking in Slovakia - Trojanova, Maria; Zgutova, Katarina; Pepucha, Lubomir; Pitonak, Martin (Communications - Scientific Letters of the University of Zilina, 2010)
The overall implementation of active benchmarking - the transfer and implementation of good practice in a closed circle in inter-laboratory comparisons its one of his components. To ensure that mission it's been created inter-laboratory comparisons model for benchmarking - and as a support web system. The system is open to different types of quality indicators and its c showing basics compliance with accreditation requirements.
Keywords: no keywords